2005
DOI: 10.1111/j.0041-1132.2005.04342.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in concentration of prion protein in the peripheral blood of patients with variant and sporadic Creutzfeldt‐Jakob disease detected by dissociation enhanced lanthanide fluoroimmunoassay and flow cytometry

Abstract: There are differences in free and cell-associated PrP found in blood of CJD patients and control groups, some of which might be useful with other tests in disease profiling as an aid to diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…In contrast to an earlier report (45), we were able to detect low levels of PrP C expression using the sandwich CDI on purified granulocytes, monocytes, CD4 + T cells, CD8 + T cells, B cells, and platelets (Fig. 4).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to an earlier report (45), we were able to detect low levels of PrP C expression using the sandwich CDI on purified granulocytes, monocytes, CD4 + T cells, CD8 + T cells, B cells, and platelets (Fig. 4).…”
Section: Discussioncontrasting
confidence: 99%
“…3) (45, 46), we hesitate to assign importance to this finding for several reasons. First, our sample size was small ( n =3-5) and second, the differences were only statistically significant after a small subpopulation of platelets with an uncharacteristically high level of PrP (172,806 ± 25,504) was excluded from the analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The observed change in CD230 fluorescence was, however, not detectable in our macaques when samples were stained with MoAb 3F4. This agrees with findings of 3F4‐stained blood samples from vCJD patients 37 . Thus, it is tempting to speculate that conformational changes were the underlying mechanism in our study, too, as was described in in vitro 5 and in in vivo models 6 .…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in PrP might be predicted by neuronal loss, but its alteration in the remaining neuronal population suggests a pathological change in antigen density. It has recently been reported that PrP C , as detected by dissociation-enhanced lanthanide fluorescent immunoassay (DELFIA), is reduced in whole blood samples of variant Creutzfeldt-Jakob disease patients and non-TSE neurological patients; however, this decrease may be off-set by an increase of PrP C in platelet-depleted plasma, suggesting a change in blood 'compartmentalization' of PrP C rather than the reduction observed here at the surface of brain cells [18]. Increased GFAP staining was noted in methanolfixed prion-infected brain cells of TSE-infected mice, consistent with activation and proliferation of astrocytes.…”
Section: Discussionmentioning
confidence: 61%